A Review of Oxidative Stress and Urinary Dysfunction Caused by Bladder Outlet Obstruction and Treatments Using Antioxidants - Yasuyoshi Miyata; Tomohiro Matsuo; Kensuke Mitsunari; Akihiro Asai; Kojiro Ohba; Hideki Sakai (MDPI AG, 2019)
Urinary dysfunction is a common pathological condition that can significantly decrease the quality of life. Bladder outlet obstruction (BOO) is a major cause of urinary dysfunction, and various lower urinary tract diseases including benign prostatic hyperplasia and urethral stricture disease cause BOO. According to the results of a variety of animal experiments on partial BOO (PBOO), there is a general agreement that ischemic conditions and repeated ischemia/reperfusion of the bladder are closely associated with BOO-induced bladder damage, and that increased oxidative stress by ischemia/reperfusion plays a crucial role in the pathological mechanisms underlying urinary dysfunction. Changes in biomarkers of oxidative stress in PBOO animal models support this association between oxidative stress and urinary dysfunction. Oxidative stress is defined as an imbalance between the production of pro-oxidants, such as free radicals and reactive species, and their elimination through protective mechanisms of antioxidants. Therefore, organizing the knowledge on the state of oxidative stress, changes in biomarkers, and biological roles of antioxidants in systemic and bladder tissues is essential to understand the detailed pathological characteristics of the urinary dysfunction caused by PBOO. Furthermore, information on drugs and supplements that have antioxidant effects is important for defining treatment strategies for urinary dysfunction with PBOO. In this review, we paid special attention to the following three issues; (1) changes in oxidative stress, including its biomarkers, (2) antioxidant status, and (3) previous reports on treatment strategies involving agents with antioxidative activity for urinary dysfunction caused by BOO. In particular, we provide systematic information on the detailed mechanisms underlying the antioxidative effects of agents used to treat PBOO. In addition, we show present research issues and research limitations, as well as suggest possible future antioxidant treatment strategies for patients with PBOO.